Anti-Aging Potential of Avocado Oil via Its Antioxidant Effects - Olin Torres-Isidro; Marcela González-Montoya; Manuel Alejandro Vargas-Vargas; Ulises Florian-Rodriguez; Claudia Isabel García-Berumen; Rocío Montoya-Pérez; Alfredo Saavedra-Molina; Elizabeth Calderón-Cortés; Alain Raimundo Rodríguez-Orozco; Christian Cortés-Rojo (Pharmaceuticals)
Aging is a process characterized by tissue degeneration, increased susceptibility to chronic degenerative diseases, infections, and the appearance of neoplasms, which leads to disability and a reduction in the length and quality of life. This phenomenon is the result of the convergence of multiple processes, including mitochondrial dysfunction, fibrosis, inflammation, dysregulation of cell death processes, and immunosenescence. These processes have as their point of convergence an increase in the production of ROS. Avocado oil (Persea americana Mill.) contains a diverse array of bioactive compounds, including oleic acid, phytosterols, chlorophylls, xanthones, xanthines, and carotenoids. These bioactive compounds have the capacity to modulate the excessive production of ROS, thereby reducing the progression of age-related diseases and extending lifespan in experimental models of aging. In addition, several studies have demonstrated the efficacy of avocado oil in mitigating age-related diseases, including hypertension; insulin resistance; diabetes; non-alcoholic liver disease; and degenerative processes such as hearing loss, cognitive decline, neurodegeneration, and impaired wound healing. In light of these findings, it is hypothesized that avocado oil is a promising agent capable of promoting healthspan in later stages of life owing to its direct antioxidant actions and the activation of pathways that enhance endogenous antioxidant levels.